Economic Instruments and Induced Innovation: The Case of End-of-Life Vehicles European Policies - Massimiliano Mazzanti; Roberto Zoboli (Fondazione Eni Enrico Mattei (FEEM), 2005)
The paper addresses the dynamic-incentive effect of environmental policy instruments when innovation is uncertain and occurs in very complex industrial subsystems. The case of end-of-life vehicles (ELVs) is considered focusing predominantly on the effects of the European Directive adopted in 2000 which stipulated economic instruments as free take-back, and on the voluntary agreements in place in many EU countries. The ELV case study is an example of a framework where policy-making faces an intrinsic dynamic and systemic environment. Coherent sequences of single innovations taking place in both upstream (car making) and downstream (car recycling/recovery) of the ELV system can give rise to different innovation paths, in accordance with cost-benefit considerations, technological options and capabilities associated to the different industrial actors involved. The impact of economic instruments on innovation paths, in particular free take-back, is considered. Deficiencies or difficulties concerning the transmission of incentives between different industries can prevent the creation of new recycling/recovery/reuse markets, giving rise to other less preferable and unexpected outcomes. The implication for policy is a need for an integrated policy approach, as enforceable VAs, in order to create a shared interindustry interest for innovation and to reduce the possible adverse effects which economic instruments exert on innovation through cost benefit impacts on key industrial and waste-related agents involved in the ELV management system. These advantages should be taken into account vis à vis the emergence of Integrated Product Policy (IPP) as a leading concept of EU environmental policy and the associated shift from extended producer responsibility to extended product responsibility.
Keywords: L62; O13; O31; O38; 330; ELV; Induced innovation; Dynamic efficiency; Economic instruments; Recycling; Umweltpolitik; Produktlebenszyklus; Kraftfahrzeug; Kreislaufwirtschaft; Endogener technischer Fortschritt; EU-Staaten